Sistem Pakar Diagnosa Penyakit Trichomoniasis Menggunakan Metode Certainty Factor - Dwi Nurul Huda; Selly (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
Trichomoniasis or trich is an infection in vagina that causes by a protozoa called trichomonas vaginalis. Trich got contagious by sexual activity. This disease attacking the underneath of genital of man or woman, on the part that called tractur urogenitalis. Most of people feel shy to do a consultation with doctor about their genital because it’s too privacy for them, and also there’s an economic factor if they do a consultation with a doctor, because it’s not free and definitely needs more charge to spend. With this expert system, users who suffer from diseases are not ashamed because they can diagnose the disease themselves, and can also save on consultation fee. The methodology used for the development of this application is waterfall methodology, the reason is because this application was designed from scratch, so the author feels that this methodology is very appropriate to be applied in the process of developing this expert system. And for the calculation method in this expert system, the author uses the certainty factor method which is a method commonly used in expert system. The outcome of this thesis is there’s a system that can diagnose what percentage is the possibility of someone got infected by trich depending on the choice of symptoms they entered into the program. This expert system was built using Netbeans IDE 8.0 and MySQL as the database.